Conocimientos y prácticas sobre la prevención de las infecciones respiratorias agu- das en las madres de niños menores de cinco años, atendidas en el Centro de Salud “Virgen del Rosario de Carapongo” Lima, julio de 2010 - Luna Mamani, Nancy (2019)
Objective: Assess knowledge and practices on the prevention of infections infections in mothers of children under 5 years treated at the Center Health Virgen del Carmen, 2011. Methods: The study is descriptive, transversal.The study populations were 130 mothers with children under 5 years. Technique was used as the interview, and asthe survey instrument was used and applied in person to each mother by the researchers. Results: On the level ofknowledge 70% of mothers of children under five has a regular level of knowledge regarding acute respiratory infections, 16.2% 13.8% good and a poor level. As for practices, 52.1% of mothers of children under five are improperpractices in the prevention of acute respiratory infections while 47.8% if you practice. Conclusions: Was identified that the knowledge about the prevention of acute respiratory infections are associated with age and number ofchildren. It was also determined that there is no significant relationship between knowledge and practice. We alsoidentified that there is greater willingness of mothers of learning about the prevention of acute respiratory infectionsconsidering the specific levels of the predictor variables according to (RM).